Saliva of Ixodes ricinus enhances TBE virus replication in dendritic cells by modulation of pro-survival Akt pathway - Lieskovská, Jaroslava; Páleníková, Jana; Langhansová, Helena; Chmelař, Jindřich; Kopecký, Jan (Virology, 2018)
It has been suggested that tick saliva facilitates transmission of tick-borne encephalitis virus (TBEV) to vertebrates. The mechanism of this facilitation has not been elucidated yet. Since dendritic cells (DCs) are among first cells attacked by the virus, we examined the amount of virus and changes induced by saliva in TBEV-infected DCs. We found that virus replication was significantly increased by saliva of Ixodes ricinus tick. Next, saliva-induced enhancement of Akt pathway activation was observed in TBEV-infected DCs. Akt mediated pathway is known for its anti-apoptotic and pro-survival effects. Accordingly, apoptosis of TBEV-infected DCs was declined and cellular viability increased in the presence of tick saliva. Saliva-induced enhancement of STAT1 and NF-κB was also observed in TBEV-infected DCs. In conclusion, we suggest that tick saliva provides pro-survival and anti-apoptotic signals to infected DCs via upregulation of Akt, which may have positive consequences for TBEV replication and transmission.
Keywords: Animals; apoptóza; Tick saliva; Female; Proto-Oncogene Proteins c-akt; transkripční faktor STAT1; arachnida jako vektory; klíště; Apoptosis; ženské pohlaví; Dendritic Cells; sliny; dendritické buňky; Dendritic cells; lidé; replikace viru; Mice; viry klíšťové encefalitidy; myši; morčata; protoonkogenní proteiny c-akt; Encephalitis Viruses, Tick-Borne; Signaling; Saliva; STAT1 Transcription Factor; Encephalitis, Tick-Borne; Guinea Pigs; zvířata; klíšťová encefalitida; Arachnid Vectors; Mice, Inbred C57BL; Virus Replication; TBEV; Ixodes; myši inbrední C57BL; Humans